Foot self-care practices of adults with diabetes mellitus - Fuentes, Raya Kathreen T.; Domingo, Christian Owen P.; Durana, Kaisha V.; Evangelista, Kristine Chelsea Shynne M.; Feliciano, Nicole A.; Ferido, Kathleen Patricia Q.; Ferrer, Christianna Joy J. (Manila College of Nursing University of the Philippines Manila, 2017)
Diabetes mellitus is a global public health concern. Foot ulcer is one of the most serious and costly complications of diabetes mellitus. Among the components of diabetes self-management, foot self-care was found to be one of the best preventive measures for foot
ulcers yet is seldom performed. Thus, the purpose of this study was to determine how
adequate foot self-care practices were among Filipino adults with diabetes mellitus with the
following objectives: (1) describe their foot self-care practices; (2) determine their overall
diabetes self-management; (3) determine the relationship between foot self-care practices and
overall diabetes self-management, and (4) determine the relationship of foot self-care
practices to diabetes knowledge, diabetes social support, sociodemographic characteristics,
and disease-related characteristics.

A descriptive correlational design was utilized for the study. A self-administered questionnaire was used which had the following parts: Nottingham Assessment of Functional Footcare, Diabetes Self-Management Questionnaire, Diabetes Knowledge Questionnaire, Diabetes Social Support Questionnaire, and a general information sheet. The subjects were selected through purposive sampling with inclusion criteria of: (1) diagnosed with diabetes mellitus and (2) aged 19-65 years old. Exclusion criteria were: (1) acutely ill or in a medical emergency; (2) have comorbidities unrelated to diabetes mellitus; and (3) have any condition that would prevent the participants from performing foot self-care or from participating and completing the procedure of the study. A total of 114 respondents consented to participate coming from 3 specialized diabetes clinics and 3 outpatient clinics in National Capital Region and Central Luzon.

Results showed that majority of the respondents had adequate foot self-care practices
(M=54.65, SD=+/-6.65). Areas of foot self-care that were satisfactory included Foot Hygiene
and Foot Warming Habits while areas that were unsatisfactory included Footwear Selection,
Foot & Footwear Inspection and Wound Care. For the overall diabetes self-management,
findings showed that the mean score of the respondents was more than half of the highest
possible score (M=26.72, SD=+/-6.55). Results further revealed a significant association between foot self-care practices and overall diabetes self-management (x2 = 5.0533,
p=0.02458). Further analysis was done by separating the responses of patients coming from
3 specialized diabetes clinics and 3 non-specialized clinics. Results showed a significant
association between the foot self-care practices and overall diabetes self-management of
patients from specialized diabetes clinics (x? = 6.4368, p=0.011178).

There was no sufficient evidence to show that there was a relationship between foot self-care practices and the variables studied: (1) diabetes knowledge; (2) diabetes social support; (3) sociodemographic characteristics (age, sex, educational attainment, employment); and (4)- disease-related characteristics (type of diabetes neice, duration of disease, medications, comorbidities/complications).

Evidence suggests that good overall diabetes self-management corresponds to good foot self-care practices. Thus, reiteration of health education and continuous motivation is vital to further strengthen the patients’ compliance, correct any misconceptions, and enhance patient empowerment regarding self-care.
Accomplishment report (In partial fulfillment of the requirements for N121.2: Intensive Nursing Experience) -- University of the Philippines Manila, June 2017.
Keywords: Intensive nursing experience